An Overview of Portuguese Olive Oils and Table Olives with Protected Designation of Origin. Issue 5 (6th March 2019) - Albuquerque, Tânia Gonçalves; Costa, Helena S.; Oliveira, Maria Beatriz P. P.
Abstract : Over the years, consumers' interest in the diet and health relationship has increased with a demand for high quality foods. To protect consumers, but also producers from unfair practices, European Union (EU) has launched legislation on different EU quality schemes, namely Protected Designation of Origin (PDO), Protected Geographical Indications (PGI), and Traditional Speciality Guaranteed (TSG). This work provides an overview of research concerning Portuguese PDO olive oils and table olives. EU quality schemes applied to agricultural products and foodstuffs are increasing over the years, Portugal being the fourth European country with the highest percentage of registered foods. Up to now, Portugal has registered six olive oils and two table olives as PDO. There is a lack of physicochemical data for Portuguese PDO olive products, especially for table olives. Nonetheless, differences linked to the origin of the olive oils are reported, including within the same region of origin. For instance, a range between 95.9 and 260 mg kg −1 for α‐tocopherol was reported for PDO Azeite de Trás‐os‐Montes, while for PDO Azeites do Norte Alentejano it varied from 92.6 to 198 mg kg −1 . Further studies, especially concerning parameters that allow confirming the authenticity and origin of Portuguese PDO olive oils and table olives, are crucial. Practical Applications : Six olive oils and two table olives from Portugal are already registered with PDO. Phytochemical data for these products is scarce. Further studies to evaluate authenticity are needed. Of the table olives and olive oils already registered with Protected Designation of Origin (PDO), there are eight products belonging to the five main regions of Portugal ( Trás‐os Montes, Beira Litoral, Beira Interior, Ribatejo, and Alentejo ). Furthermore, these PDO products are linked to the history and cultural heritage of these places, being crucial for some local producers and for consumers. Abstract : Of the table olives and olive oils already registered with Protected Designation of Origin (PDO), there are eight products belonging to the five main regions of Portugal ( Trás‐os Montes, Beira Litoral, Beira Interior, Ribatejo, and Alentejo ). Furthermore, these PDO products are linked to the history and cultural heritage of these places, being crucial for some local producers and for consumers.